Edward Nealy Kellogg and Edward Stanley Kellogg papers - Kellogg, Edward Nealy, 1841-1874.; Kellogg, Edward Stanley, 1870-1948.
Biographical data, commissions, orders to duty, and miscellaneous material relating to the naval careers of Edward Nealy Kellogg and his son, Edward Stanley Kellogg. Subjects include the Battle of Mobile Bay, Ala., 1864. Edward Nealy Kellogg's private journal contains notes and poems about the sea and sea life, drawings of ships and riggings, newspaper clippings, and pressed flora.
Naval officers.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: United States. -- Navy -- Sea life; Mobile Bay, Battle of, Ala., 1864.; Naval architecture; Alabama -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Naval officers